Use of Modelica language to simulate electrified railway lines and trains. (2nd May 2019) - Ceraolo, M.; Lutzemberger, G.
Summary: Simulation of multi‐engineering systems typically requires many issues to be solved, which are to be addressed by developing appropriate modeling and simulation programming techniques. In the last years, the authors have participated in several studies in which they analyzed in detail electrified railway systems and simulated them using Modelica language. After a few years of study, despite the huge complexity of these systems, it has appeared evident that Modelica language is very well suited and able to effectively solve the typical issues they present. While specific railway system simulations have already been discussed in specific papers, whose focus was on application and actual results, in this paper, the authors show how to use Modelica language to solve specific modeling issues through suitable programming techniques. Moreover, the issues to be solved and the conceived techniques may be interpreted in a general way and to be applied also in different engineering domains. Finally, this paper briefly recalls the principal results obtained in previous specific papers, in which these techniques were fully implemented.